Exploration of Meaning in the Poem Al-I’tiraf by Abu Nawas Based on Riffaterre’s Semiotic Analysis - Nashihah, Halimatun (Journal of Arabic Language Studies and Teaching, 2024)
Abu Nawas is considered to be one of the greatest poets of classical Arabic literature, whose life was previously controversial, but when he repented, the poem Al-I’tiraf was created. And his famous poem is still recited today because it has its power for Muslims. Therefore, the researcher aims to study the hidden meanings in the lyrics of the poem Al-I’tiraf by Abu Nawas, using Riffaterre’s semiotic theory analysis. This research uses descriptive qualitative methods. The result of this study is that the matrix in this poem is found to be the hope of a servant, then the model is repentance and forgiveness, and its variants are found in the second, third, fourth, fifth, and sixth stanzas. The potential hypogram in the context of the poem Al-I’tiraf, which reflects the hope of a servant refers to the deep aspirations and desires of a servant of Allah which are reflected in the confession of sin and request for repentance. Actual hypogram in the Qur’an in surah al-Anbiyah’ verse 87 and Hadits narrated by Imam Muslim.